Bile salt hydrolase, the member of Ntn-hydrolase family: differential modes of structural and functional transitions during denaturation - Kumar, R. Suresh; Suresh, C. G.; Brannigan, James A.; Dodson, Guy G.; Gaikwad, Sushama M. (IUBMB Life, 2007)
Conformational transitions and functional stability of the bile salt hydrolase (BSH; cholylglycine EC: 3.5.1.24) from Bifidobacterium longum (BlBSH) cloned and expressed in E. coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and CD spectroscopy. Thermal and Gdn-HCl-mediated denaturation of BlBSH is a multistep process of inactivation and unfolding. The inactivation and unfolding of the enzyme was found to be irreversible. Enzyme activity seems sensitive to even minor conformational changes at the active site. Thermal denaturation as such did not result in any insoluble protein aggregates. However, on treating with 0.25-1 M Gdn-HCl the enzyme showed increasing aggregation at temperatures of 40-55 degrees C indicating more complex structural changes taking place in the presence of chemical denaturants. The enzyme secondary structure was still intact at acidic pH (pH 1-3). The perturbation in the tertiary structure at the acidic pH was detected through freshly formed solvent exposed hydrophobic patches on the enzyme. These changes could be due to the formation of an acid-induced molten globule-like state.
Keywords: Aggregation; Bile salt hydrolase; molten-globule; Unfolding

Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase

Structure of highly active BSH enzyme with subordinated post-translational excision - Chand, Deepak; Panigrahi, Priyabrata; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Bile salt hydrolase; Mutagenesis; X-ray crystallography

Highly active bile salt hydrolase from enterococcus faecalis shows positive cooperative kinetics - Chand, Deepak; Ramasamy, Sureshkumar; Suresh, C. G. (Process Biochemistry, 2016)
Bile salt hydrolase (BSH; cholylglycine hydrolase, EC 3.5.1.24) is an important enzyme that catalyses the deconjugation of bile acids conjugated with glycine or taurine and assists in the reduction of blood cholesterol levels. In the present study, we report the cloning, overexpression and characterisation of BSH gene from a gut-associated microbe Enterococcus faecalis (EfBSH). The overexpressed protein in Escherichia coli was purified to homogeneity. Optimum pH and temperature for activity were found to be 5.0 and 50 degrees C, respectively. The enzyme was considerably stable in the pH range of 5.0-7.0 and at a temperature of up to 50 degrees C. It showed high specific activity of 1390 U mg(-1) and 1289 U mg-1 for substrates such as glycocholic acid (GCA) and glycodeoxycholic acid (GDCA), respectively. The effect of additives on enzyme activity was assessed, and the detergent Triton X showed a marginally enhanced activity. The enzyme demonstrated unique enzyme kinetics of non-linear regression, thereby displaying positive cooperativity. In addition, the modulating effect of the non-substrate ligand Pen V on the hydrolysing ability of EfBSH towards bile acid such as GDCA was measured. It was observed that Pen V significantly enhanced the BSH activity. This is markedly different from the previously reported competitive inhibition of BSH activity by Pen V. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Allosteric regulation; Bile acids; Bile salt hydrolase; Enzyme kinetics; Gut organism; Penicillin V acylase

Structure and function of a highly active Bile Salt Hydrolase (BSH) from Enterococcus faecalis and post-translational processing of BSH enzymes - Chand, D. (Biochim Biophys Acta., 2018)
Bile Salt Hydrolase (BSH), a member of Cholylglycine hydrolase family, catalyzes the de-conjugation of bile acids and is evolutionarily related to penicillin V acylase (PVA) that hydrolyses a different substrate such as penicillin V. We report the three-dimensional structure of a BSH enzyme from the Gram-positive bacteria Enterococcus faecalis (EfBSH) which has manifold higher hydrolase activity compared to other known BSHs and displays unique allosteric catalytic property. The structural analysis revealed reduced secondary structure content compared to other known BSH structures, particularly devoid of an anti-parallel β-sheet in the assembly loop and part of a β-strand is converted to increase the length of a substrate binding loop 2. The analysis of the substrate binding pocket showed reduced volume owing to altered loop conformations and increased hydrophobicity contributed by a higher ratio of hydrophobic to hydrophilic groups present. The aromatic residues F18, Y20 and F65 participate in substrate binding. Thus, their mutation affects enzyme activity. Docking and Molecular Dynamics simulation studies showed effective polar complementarity present for the three hydroxyl (-OH) groups of GCA substrate in the binding site contributing to higher substrate specificity and efficient catalysis. These are unique features characteristics of this BSH enzyme and thought to contribute to its higher activity and specificity towards bile salts as well as allosteric effects. Further, mechanism of autocatalytic processing of Cholylglycine Hydrolases by the excision of an N-terminal Pre-peptide was examined by inserting different N-terminal pre-peptides in EfBSH sequence. The results suggest that two serine residues next to nucleophile cysteine are essential for autocalytic processing to remove precursor peptide. Since pre-peptide is absent in EfBSH the mutation of these serines is tolerated. This suggests that an evolution-mediated subordination of the pre-peptide excision site resulted in loss of pre-peptide in EfBSH and other related Cholylglycine hydrolases.
Keywords: autocatalytic processing; Bile salt hydrolase; molecular dynamics; Mutagenesis; Polar complementarity; X-ray crystallography